Stock exchange self-listing and value effects - Otchere, Isaac (Journal of Corporate Finance, 2006)
The stock exchange industry has experienced strong competition in recent years. The commercial realities of the day have compelled some exchanges to change their ownership and governance structure from mutual to public ownership and have listed their shares on their own exchanges. This paper examines the value effects of self-listing and the attendant change in business strategy on the performance of listed exchanges. The results provide considerable support for the proposition that exchanges whose traditional sources of revenue have come under severe pressure, and those that have experienced a slow growth in net profit margin but high growth in market activities, are likely to change their ownership structure from mutual to public ownership. A comparison of the operating performance of the listed exchanges to that of a control group of non-listed exchanges shows that the self-listed exchanges have performed better than their non-listed counterparts. The self-listed exchanges also outperformed the stock market indexes and a control group of non-exchange firms that went public in the same year as the listed exchanges. I submit that better monitoring of managerial performance, the potential threat of takeover from the market for corporate control that accompanies self-listing and the reduction in agency costs associated with the mutual form of exchange contribute to unlock growth opportunities and value for the publicly traded stock exchanges.